2018
DOI: 10.1021/acs.est.8b04108
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms for Abiotic Dechlorination of Trichloroethene by Ferrous Minerals under Oxic and Anoxic Conditions in Natural Sediments

Abstract: Bench-scale experiments were performed on natural sediments to assess abiotic dechlorination of trichloroethene (TCE) under both aerobic and anaerobic conditions. In the absence of oxygen (<26 μM), TCE dechlorination proceeded via a reductive pathway generating acetylene and/or ethene. Reductive dechlorination rate constants up to 3.1 × 10–5 d–1 were measured, after scaling to in situ solid:water ratios. In the presence of oxygen greater than 120 μM, TCE dechlorination proceeded via an oxidative pathway genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(70 citation statements)
references
References 31 publications
0
67
3
Order By: Relevance
“…The long‐term significance of abiotic or biotic degradation in aquitards or other unconsolidated LPZ media relative to back diffusion has also been demonstrated experimentally (Wanner et al 2016; Schaefer et al 2018) and in modeling simulations (Chambon et al 2010; Wanner et al. 2018).…”
Section: Literature Reviewmentioning
confidence: 84%
“…The long‐term significance of abiotic or biotic degradation in aquitards or other unconsolidated LPZ media relative to back diffusion has also been demonstrated experimentally (Wanner et al 2016; Schaefer et al 2018) and in modeling simulations (Chambon et al 2010; Wanner et al. 2018).…”
Section: Literature Reviewmentioning
confidence: 84%
“…Another potential area of research is the potential for ongoing reactivity following the transition from active treatment to ambient less reducing conditions, and/or within areas downgradient of active treatment. Building on the findings by Schaefer et al (), a more complete understanding of the role of oxygen and the potential for enhanced hydroxyl radical formation to occur in these redox recovery zones (downgradient of strongly reducing treatment areas) and the long‐term behavior of engineered systems after cessation of active remediation is warranted.…”
Section: Applying Abiotic Pathways For Site Restorationmentioning
confidence: 99%
“…As another example, recent studies have demonstrated that abiotic CVOC transformation may also occur under oxic conditions via an oxidative dechlorination pathway. For example, in laboratory studies, Schaefer et al () demonstrate that iron‐mediated TCE transformation rates were higher in the presence of oxygen, and transformation rates increased with increasing solid‐phase ferrous iron content. Their results suggest aerobic oxidation may be significant at some sites, particularly near interfaces of aerobic zones; furthermore, the addition of oxygen in some settings may enhance these processes, ultimately enhancing CVOC transformation rates.…”
Section: Review Of Abiotic Transformation Processes and Recent Researchmentioning
confidence: 99%
“…As a result, abiotic CVOC transformation is much more difficult to confirm, and its significance is not easy to distinguish from other processes that contribute to bulk attenuation rates (e.g., biotransformation, diffusion, sorption). Extensive research over the past two decades has greatly increased our understanding of the processes and controlling factors for CVOC degradation by the reducing power stored in reactive iron minerals and reactive iron mineral intermediates (e.g., Assaf‐Anid & Lin, 2002; Butler & Hayes, 1999, 2000; Cheng et al, 2020; Choi et al, 2009; Culpepper et al, 2018; Devlin et al, 2009; Fan et al, 2017; He et al, 2009, 2015; Horst et al, 2019; Jeong & Hayes, 2007a, 2007b; Lee & Batchelor, 2002a, 2002b; O'Loughlin et al, 2003; Schaefer et al, 2018a; Vikesland et al, 2007; Whiting et al, 2014; Yu et al, 2018). This increased understanding offers the potential to further leverage abiotic transformation processes and increase overall bulk contaminant transformation rates; however, currently most ERD designs do not specifically consider how to maximize complementary abiotic treatment processes.…”
Section: Introductionmentioning
confidence: 99%